2020
DOI: 10.1002/micr.30654
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral breast reconstruction with the free contralateral split breast flap using supermicrosurgical anastomosis: A case report

Abstract: Abstrct Consecutive or simultaneous contralateral breast reduction is a frequent request from patients undergoing unilateral breast reconstruction. Both procedures can be combined using otherwise discarded tissue as a split breast graft for reconstruction of the contralateral side. There have been few reports on the use of pedicled split breast grafts. We present a 75‐year‐old female with multicentric mammary carcinoma following chemotherapy, mastectomy, axillary lymph node dissection and radiotherapy. She req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Scaglioni et al reported harvesting a free flap based on the IMA perforators from the contralateral breast (Scaglioni et al, 2020). Unlike in our case, the authors performed a medial incision superiorly on the chest wall and sacrificed the donor side NAC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scaglioni et al reported harvesting a free flap based on the IMA perforators from the contralateral breast (Scaglioni et al, 2020). Unlike in our case, the authors performed a medial incision superiorly on the chest wall and sacrificed the donor side NAC.…”
Section: Discussionmentioning
confidence: 99%
“…Breast‐sharing pedicled flaps from the contralateral breast have been described for many years (Marshall et al, 1981; Schoeller et al, 2001). Recently, free tissue transfer from the contralateral breast based on the thoracoacromial and internal mammary perforators has been performed (He et al, 2020; Scaglioni et al, 2020). The long thoracic artery perforator (LTAP) flap is well‐established as a pedicled flap for ipsilateral breast‐conserving surgery (Martellani et al, 2019; McCulley et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Reduction mammoplasty of the unaffected contralateral breast can help achieve breast symmetry in patients with a hypertrophic and ptotic breast. Previous studies have reported about breast reconstruction using a pedicled or free flap harvested from tissues commonly disposed in reduction mammoplasty of the unaffected breast (Caggiati et al, 2017; Dian et al, 2009; Geerards et al, 2018; He et al, 2020; Holdsworth, 1956; Kalender & Guliyeva, 2020; Lopez et al, 2020; Marshall, 1993; Marshall et al, 1981; Mayer et al, 2016; Morritt et al, 2006; Novo‐Torres et al, 2015; Pontes, 1973; Scaglioni et al, 2020; Schoeller et al, 2001; Sharp et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Two approaches are used in this technique. That is, the contralateral unaffected breast is dissected into half either vertically (Dian et al, 2009; Geerards et al, 2018; Mayer et al, 2016; Pontes, 1973; Scaglioni et al, 2020) or horizontally (Caggiati et al, 2017; He et al, 2020; Holdsworth, 1956; Kalender & Guliyeva, 2020; Lopez et al, 2020; Marshall, 1993; Marshall et al, 1981; Morritt et al, 2006; Novo‐Torres et al, 2015; Schoeller et al, 2001; Sharp et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation